Answer:
Hey love! x = 6
Step-by-step explanation:
because 13 x 6 = 78
HOPE THIS HELPS!
1.1x+1.2x-5.4=-10
11/10x+12/10x-54/10=10
11x/2.5+2^2-1*3/5x-3^3/5=-10
(11x)+2(2*3x)+2(-3^3)/2*5=-10
11x+2(6x)+2(-27)/2*5=-10
11x+2*6x-2*27/2*5=-10
11x+12x-54/2*5=-10
23x-54/2*5=-10
23x-54=-100
23x=-46
23x/23=-46/23
x=-2*23/23
x=-2
Answer:
= ![\frac{3}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7B2%7D)
![(3-x)](https://tex.z-dn.net/?f=%283-x%29)
Step-by-step explanation:
let the number be x , then :
six added to twice the sum of a number and four means :
![6 + 2 (x+4)](https://tex.z-dn.net/?f=6%20%2B%202%20%28x%2B4%29)
one half of the difference of three and the number means :
![\frac{3}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7B2%7D)
![(3-x)](https://tex.z-dn.net/?f=%283-x%29)
combining the two , we have
= ![\frac{3}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7B2%7D)
![(3-x)](https://tex.z-dn.net/?f=%283-x%29)